The Arterial System of the Fasciocutaneous Deltoid Flap Pedicle on 320-Detector Row Computed Tomography and Clinical Application in the Foot and Hand - Ngoc-Huyen, Nguyen; The-Hoang, Nguyen; Lam, Khanh; Quang-Vinh, Nguyen; Staudenmaier, Rainer (Journal of Reconstructive Microsurgery, 2024)
Background Fasciocutaneous free deltoid flaps are used to reconstruct hand, foot, and maxillofacial defects. Although anatomical studies of this flap pedicle have been performed on cadavers, there are no reports on the use of 320-detector row computed tomography angiography (CTA-320) to investigate the deltoid flap pedicle in living humans. This study aimed to investigate the arterial characteristics of the deltoid flap pedicle using the CTA-320 system in living humans.Methods Twenty-seven adult Vietnamese patients with 54 healthy deltoid regions underwent CTA-320 to investigate arterial blood supply before clinical free-flap transfer. Two- and three-dimensional reconstruction images of the arterial pedicle were visualized, and clinical reconstruction results were evaluated.Results The cutaneous vessel branches of the deltoid flap were separated from the posterior circumflex humeral artery (PCHA) and originated from the axillary (77.78%), subscapular (12.96%), and brachial (9.26%) arteries. The PCHA penetrated the quadrangular space in 90.74% of patients. The cutaneous arterial branch was present in the deltoid-triceps groove in 100% of patients. The average diameter and length of the PCHA were 3.38 ± 0.58 and 43.08 ± 6.60 mm, respectively. The average diameter and length of the flap cutaneous branch were 1.49 ± 0.28 and 44.57 ± 4.83 mm, respectively. The findings of CTA-320 were aligned with the intraoperative clinical findings well. All deltoid flaps were successfully free-transferred with good outcomes.Conclusion The CTA-320 is a practical and effective method for investigating deltoid flap pedicles. It enables accurate flap design and harvesting of flaps, thereby enhancing the clinical success of free-flap transfer.
Keywords: deltoid flap pedicle; CTA-320 method; free-flap transfer; soft tissue defect reconstruction